Study on power distribution network automation to mitigate power outages - Habtu Gebremeskel , Dawit; Biru Worku, Getachew (Zede Journal of Ethiopian Engineers and Architects, 2023)
The paper presents development of an appropriate distribution system automation to mitigate power outages and improve reliability of the system. Addis Ababa distribution system is taken as a case study to demonstrate the effectiveness of the proposed technique. It is found that 55% of the number of interruptions and 46% of the total duration of interruptions in the existing Addis Ababa distribution system are due to distribution system related problems. The proposed distribution system automation is capable of detecting feeder faults, determining the fault location, isolating the faulty section of the feeder and finally restoring power supply to healthy portions of the feeder. Thus, it has the capacity to significantly improve the reliability of the distribution system. The performance of the designed model is evaluated through simulation studies to check the reliability improvement of Addis Ababa distribution network. The simulation results show that the System Average Interruption Duration Index (SAIDI) and System Average Interruption Frequency Index (SAIFI) is improved by 69% and 88%, respectively. Thus, it is observed that the frequent interruptions and outages in the existing Addis Ababa distribution system could be potentially mitigated by implementing the proposed automation of Addis Ababa distribution network.